Evolution of views on judicial policy in the context of judicial law - R. A. Kalarash (Law and Safety)
The article examines various aspects of understanding judicial policy, which is an important component of the judicial law doctrine, including analysis of court procedures, formation of the judiciary, strategic planning of court actions, setting priorities in law enforcement practice, and ensuring accessibility and efficiency of justice. It also analyses the genesis of scientific approaches to understanding judicial policy within the doctrine of judicial law through the historical stages of legal science development. It covers the period from classical legal theories to modern trends in the transformation of the judicial system, providing a unique overview of the evolution of this key concept in legal science. The evolutionary path of understanding judicial policy is explored through the analysis of concepts, theories and methodologies that trace the changing role of the judiciary in society and the formation of strategies for managing the judicial system. The classical school of law, which emphasised the principles of justice and legality, further development of theories of judicial activism and legal realism, as well as modern concepts which take into account the issues of efficiency, transparency and publicity of judicial activity in a legal democracy are considered. The historical documents and scientific works of different periods and civilisations are analysed to study the emergence, formation and development of judicial policy in the context of a single comprehensive doctrine of the judiciary. The research identifies the key aspects and paradigms which had a decisive impact on the formation of the modern understanding of judicial policy. The author substantiates the importance of studying this topic for the development of legal science and practice, especially in the context of ensuring justice and protection of human rights. The prospects for further development of judicial policy are outlined, taking into account the current challenges and needs of society for effective justice. The importance of researching this topic for the development of legal science and practice, especially in the context of ensuring justice and protection of human rights, is argued.